IMPLEMENTATION GREEN BUILDING'S FUNCTIONS AS AN ALTERNATIVE WOOD COMPONENTS - M. Alvan Rizki (Journal of Geography, Regional Planning and Development, 2024)
Construction waste becomes a major problem in a construction project, an attempt to reduce the volume of wood waste by reusing wood waste into other material objectives and benefits of writing this article are: 1. Knowing how to realize green building by utilizing wood construction waste 2. Knowing How to recommend ways to reduce wood building waste at the time of implementation of building construction. The method used in this article is the study of literature related to wood construction waste. The data analyzed is obtained from various sources of literary research, including journals, writings from the Internet, and secondary datasets related to the topic of the article. Construction waste is a major problem in a construction project because it affects the environment around the project. To do this it is necessary to do management of construction waste so as not to cause environmental problems using wood construction waste How to realize green building by utilizing wooden construction waste is by using or reusing the remainder of wood construction produced by building construction in the form of used wood the remains of the project collected then recycled as pieces of wooden boards that are assembled and polished then will be made as a frame of roof, bucket, doors and new windows